Application of the Problem-Based Learning (PBL) Model to Improving the Speaking Ability of Fifth-Grade Students - Mansyur M; Karopak, Julsari (International Journal of Elementary Education, 2025)
Undefined Learning that is still dominated by lecture methods causes students to become passive and unmotivated. As a result, students' speaking skills in Indonesian language subjects remain low. The purpose of this study is to improve the speaking skills of fifth-grade students through the application of the Problem-Based Learning model. This study is a classroom action research conducted in two cycles. The research subjects were 32 students. The research data consisted of two types, namely qualitative data using observation sheets of teacher and student activities, and quantitative data using student speaking tests. The percentage of KKTP achievement on the student speaking test in the first cycle was 52.63%, with an average of 62.93, where 24 students completed the test and 8 students did not complete it. In cycle II, the percentage of students' KKTP speaking test achievement was 84.21%, with an average of 81.32, where 30 students completed the test and 2 students did not. The Problem-Based Learning Model has a positive impact on improving fifth-grade students' speaking skills, so this Problem-Based Learning Model can be used as an alternative for teaching speaking skills in elementary schools.